Telerehabilitation and Physical Therapy: Proposal for a Therapeutic Assessment Applied to Vestibular Dysfunctions - Araújo, Lucas Barbosa de; Menezes, Karla Vanessa Rodrigues Soares; Rodolfo, Jully Israely de Azevedo; Lira, Maria das Graças de Araújo; Figueiredo Ribeiro, Karyna Myrelly Oliveira Bezerra de (International Archives of Otorhinolaryngology, 2025)
Telerehabilitation has been used in several areas of physical therapy, including for respiratory, neurological, and musculoskeletal functions of patients with coronavirus disease 2019 (COVID-19), after stroke, and after hospital discharge (respectively). However, a few studies investigated protocols for assessing vestibular dysfunctions using teleconsultation.To propose a protocol for remote physical therapy assessment of vestibular dysfunctions.A literature review on telerehabilitation in physical therapy was conducted in the PubMed and SciELO databases using the search terms telehealth, telerehabilitation, vestibular disease, dizziness, vertigo, and postural balance. Four physical therapists with experience in the vestibular rehabilitation field discussed the collected data and suggested adaptations for remote clinical and functional tests to assess patients with vestibular dysfunctions.The proposed protocol for remote assessment of vestibular dysfunctions comprised anamnesis, adaptations of nine oculomotors, two static balance, and one dynamic gait balance tests, a questionnaire assessing the impact of dizziness on quality of life, and observation of cervical mobility.The protocol may be a valuable tool to assess and monitor the care of patients with vestibular dysfunction, reducing healthcare costs for the therapist and patient and enabling the attendance of those with difficulties in traveling to the rehabilitation center or needing isolation.
Keywords: dizziness; health evaluation; telehealth; vertigo; vestibular diseases